2015
DOI: 10.1371/journal.pone.0120433
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Inflammatory Markers in Depressed Elderly Patients with Diabetes and Mild Cognitive Impairment

Abstract: ObjectiveThe aim of the study was to determine the serum levels of CRP, IL-6 and TNF-α in elderly diabetic patients with depressive syndrome alone or with coexisting mild cognitive impairment (MCI).Methods276 diabetics elders were screened for depressive symptoms (using Geriatric Depression Scale: GDS-30) and MCI (using the Montreal Cognitive Assessment: MoCA score). Data of HbA1c, blood lipids and inflammatory markers levels were collected.ResultsIn all groups of patients levels of CRP, IL-6 and TNF-α were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 54 publications
(60 reference statements)
0
57
1
3
Order By: Relevance
“…The association between levels of IL-6 and cognitive impairment in MDD has been investigated in the majority of studies addressing the impact of peripheral cytokines on cognition (Dannehl et al, 2014;Duivis et al, 2013;Elderkin-Thompson et al, 2012;Gimeno et al, 2008;Goldsmith et al, 2016a;Gorska-Ciebiada et al, 2015;Grassi-Oliveira et al, 2011;Jehn et al, 2015;Krogh et al, 2014;Matsushima et al, 2015). In these studies higher levels of IL-6 were associated with worse cognitive performance on encoding and recall in depressed and healthy elders (Elderkin-Thompson et al, 2012), psychomotor speed in medication-naïve patients with MDD (Goldsmith et al, 2016a) as well as immediate and delayed verbal recall in patients with MDD (Grassi-Oliveira et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between levels of IL-6 and cognitive impairment in MDD has been investigated in the majority of studies addressing the impact of peripheral cytokines on cognition (Dannehl et al, 2014;Duivis et al, 2013;Elderkin-Thompson et al, 2012;Gimeno et al, 2008;Goldsmith et al, 2016a;Gorska-Ciebiada et al, 2015;Grassi-Oliveira et al, 2011;Jehn et al, 2015;Krogh et al, 2014;Matsushima et al, 2015). In these studies higher levels of IL-6 were associated with worse cognitive performance on encoding and recall in depressed and healthy elders (Elderkin-Thompson et al, 2012), psychomotor speed in medication-naïve patients with MDD (Goldsmith et al, 2016a) as well as immediate and delayed verbal recall in patients with MDD (Grassi-Oliveira et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In these studies higher levels of IL-6 were associated with worse cognitive performance on encoding and recall in depressed and healthy elders (Elderkin-Thompson et al, 2012), psychomotor speed in medication-naïve patients with MDD (Goldsmith et al, 2016a) as well as immediate and delayed verbal recall in patients with MDD (Grassi-Oliveira et al, 2011). In the study of diabetic elders, higher levels of IL-6 predicted higher likelihood of having been diagnosed with mild cognitive impairment (MCI) (Gorska-Ciebiada et al, 2015). Another study on depressed cancer patients revealed that IL-6 levels was negatively correlated with the Brain-Derived Neurotrophic Factor (BDNF) levels (Jehn et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…including central nervous system impairment [45,46]. The chronic inlammatory status may contribute to vessel wall changes (endothelial dysfunction, stifening of arteries and arterioles and impaired vascular reactivity) and may also have neurotoxic efects: synaptic dysfunction and neural cell apoptosis [46][47][48][49].…”
Section: Copd: Fundamental Pathophysiological Mechanisms Susceptible mentioning
confidence: 99%
“…Despite the clear link between cognitive impairment and diabetes disorders in epidemiologic studies, relatively little is known about the mechanism that underlies this association. A lot of studies had suggested that cognitive dysfunction in diabetes could be connected with severe hypoglycemia or persistent hyperglycemia, depression, inflammation, an increased prevalence of macrovascular and microvascular disease [6,7]. All these vascular etiology factors can interfere with other neurological changes in the aging brain and worsen the cognition [8].…”
Section: Introductionmentioning
confidence: 99%